VD_FINDINFO HC / 2012 / 496 vom 5. Juli 2012 - VD Tribunal cantonal (2012)
INVENTAIRE, MASSE SUCCESSORALE, SUCCESSION | 553 al. 1 ch. 3 CC, 489 CPC, 525 CPC, 41 al. 5 LMSD, 42 al. 1 LMSD, 405 al. 1 CPC (CH), 104 CDPJ, 111 CDPJ, 166 al. 2 CDPJ